Archival research in translation and censorship: Digging into the “true museum of Francoism” - Lobejón Santos, Sergio; Castro, Cristina; Gutiérrez Lanza, Camino (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
Systematic research on translation and censorship in Francoist Spain started roughly ten years after the dismantling of the regime’s censorship apparatus in 1985, following the opening of the censorship archives at the Archivo General de la Administración (AGA) in Alcalá de Henares. Since then, numerous comprehensive studies on the translation of various genres have been produced, all of them making extensive use of the censorship files issued and archived by the regime as their main source of information. However, little to no reflection has been done on the structure, usefulness and reliability of those data. This paper examines archival sources in translation and censorship, delving into the AGA’s history and structure, as well as its unique position as a censorship repository. It describes the AGA’s document collections on censored cultural artefacts and the possibilities they afford to study the impact of censorship on the translation of various text types. Ultimately, it argues that while AGA data have proved to be a key component in censorship research in Spain, complementary information is essential in reconstructing translation activity at the time and to ascertain how textual changes observed in censored translations came about.